(untitled) (Journal of Social Sciences Review, 2022)
The Panama Leaks issue has created a hassle in the whole world, naming individuals, groups and companies. The issue has been equally chanted in the Pakistani Media, both print as well as electronic. Through this issue, individuals having major positions both at an official and national level have been put under fire. The Editorials written by both Daily Dawn and The News represent an insightful analysis and give their expert opinion on the issue. According to McCombs (1972), it is the role of the media to present the interesting aspects of the political parties and to convey the reason for a political campaign to gather public support. Van Dijk (1997) has provided his model for Critical Discourse Analysis in which he has illustrated some of the categories which, according to him, are essential for CDA studies. He is of the view that it often happens that the writer sometimes hides the agent and his identity if the agent is doing something wrong. He has given the concept of self and others. The newspapers framed two major ideologies one was of PTI, and the other was of PML-N. PTI’s ideology was to hold a strong opposition to the case leaving no way out for the Sharifs. On the other hand, Sharif’s announced their resolve to accept the decision of the court amid strong opposition.